Blackened Faces and a Veiled Woman: The Early Korčula Moreška - Čale Feldman, Lada (2004)
The purpose of the paper is twofold: to develop a coherent account of the early history of the moreška in Korčula and its possible antecedents elsewhere ; and to show that in Korčula, too, a hidden transcript of resistance to external rule was insinuated into the imported narrative of Turks, Moors, and Christians.